Markers of Tissue Repair and Cellular Aging Are Increased in the Liver Tissue of Patients With HIV Infection Regardless of Presence of HCV Coinfection. (11th June 2018) - Naggie, Susanna; Swiderska-Syn, Marzena; Choi, Steve; Lusk, Sam; Lan, Audrey; Ferrari, Guido; Syn, Wing-Kin; Guy, Cynthia D; Diehl, Anna Mae
Abstract: Liver disease is a leading cause of HIV-related mortality. Hepatitis C virus (HCV)–related fibrogenesis is accelerated in the setting of HIV coinfection, yet the mechanisms underlying this aggressive pathogenesis are unclear. We identified formalin-fixed paraffin-embedded liver tissue for HIV-infected patients, HCV-infected patients, HIV/HCV-coinfected patients, and controls at Duke University Medical Center. De-identified sections were stained for markers against the wound repair Hedgehog (Hh) pathway, resident T-lymphocytes, and immune activation and cellular aging. HIV infection was independently associated with Hh activation and markers of immune dysregulation in the liver tissue.